2014
DOI: 10.1364/boe.5.001262
|View full text |Cite
|
Sign up to set email alerts
|

Reduced interhemispheric functional connectivity of children with autism spectrum disorder: evidence from functional near infrared spectroscopy studies

Abstract: Autism spectrum disorder (ASD) is a neuro-developmental disorder, which has been associated with atypical neural synchronization. In this study, functional near infrared spectroscopy (fNIRS) was used to study the differences in functional connectivity in bilateral inferior frontal cortices (IFC) and bilateral temporal cortices (TC) between ASD and typically developing (TD) children between 8 and 11 years of age. As the first report of fNIRS study on the resting state functional connectivity (RSFC) in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 49 publications
7
54
0
Order By: Relevance
“…Since language production and comprehension rely mainly on the left hemispheric networks [26], three seeds, locating respectively at the left superior (Ch4), middle (Ch6) and inferior (Ch8) temporal gyrus, were selected for generating correlation maps. The weaker RSFC in ASD revealed here is in line with a previous fNIRS study but where less number of subjects were involved (i.e., 10 ASD + 10 TD) [10]. Bilaterally symmetric pair wise correlation values for HbO 2 and Hb were also calculated for each group and illustrated in Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Since language production and comprehension rely mainly on the left hemispheric networks [26], three seeds, locating respectively at the left superior (Ch4), middle (Ch6) and inferior (Ch8) temporal gyrus, were selected for generating correlation maps. The weaker RSFC in ASD revealed here is in line with a previous fNIRS study but where less number of subjects were involved (i.e., 10 ASD + 10 TD) [10]. Bilaterally symmetric pair wise correlation values for HbO 2 and Hb were also calculated for each group and illustrated in Fig.…”
Section: Resultssupporting
confidence: 90%
“…These features make optical brain imaging very suitable to study brain function in children and other sensitive populations. A recent study using functional near infrared spectroscopy (fNIRS) in ASD showed weaker resting-state functional connectivity (RSFC) between the bilateral language areas [10]. This finding is consistent with a similar study utilizing fMRI [8].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In order to remove the the motion artifact from our study and make sure the data were qualified for analysis and interpretation, we introduced the same training procedures as our previous studies on children with ASD [16]. During the experiment, noticeable head movement and touching the optics fibers or helmet were not allowed.…”
Section: Participants and Experimental Protocolmentioning
confidence: 99%